TAM Model: Evaluation of Village Information Technology Adoption Acceptance in Kotim in the Covid-19 Pandemic Era - Rusda, Depi; Mustaqiem; Ardi Wicaksana Putra, Dwi (Politeknik Dharma Patria Kebumen, 2021)
Information technology can work with the execution of work to accomplish ideal and most extreme usage. To make government services advanced, the role of the government from the central to the regional levels is vital. The East Kotawaringin Regency Government utilizes the e-government system with the intention that all services to the community become easier and more transparent. This study examines the factors of the ease of use of village service information technology and the benefits obtained from village service information technology in terms of attitudes, desires, and real behavior by adapting the Technology Acceptance Model (TAM). This study will suggest public services, particularly town organizations required by the local area in East Kotawaringin during the Covid 19 pandemic. Information examination was done in this concentrate on utilizing the Partial Least Square (PLS) strategy utilizing WarpPLS programming form 7. The outcomes show client comfort factors, saw helpfulness, perspectives, conduct expectations, and genuine conduct have a positive and huge impact on innovation in the town.